2015
DOI: 10.1111/rda.12517
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Among Different Devices and Electrical Stimulus on the Electroejaculation of Captive Agoutis (Dasyprocta leporina)

Abstract: The interactions among different electroejaculation devices associated with serial or continuous stimuli were investigated to improve the efficiency of the electroejaculation for semen collection in agoutis. Ten sexually matured male Dasyprocta leporina were restrained by the intramuscular administration of xylazine-ketamine association. Each individual was randomly subjected to four electroejaculation protocols, by combining two devices (one presenting longitudinal electrodes emitting square waves and other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
0
20
1
Order By: Relevance
“…Additionally, Castelo et al (2016) demonstrated the interaction between different types of electrical stimuli, as sine or quadratic waves, and electroejaculation using ring or strip electrode apparatus with better results than those reported by Mollineau et al (2008Mollineau et al ( , 2010. The authors obtained 70% of ejaculates, with 57% of ejaculates containing spermatozoa, when using the protocol with the ring electrode associated with sinusoidal stimuli (Castelo et al, 2016). However, Martinez et al (2013) obtained better results using four brown agouti (D. azarae) and obtained 100% success in semen collection.…”
Section: Art For Male Agoutimentioning
confidence: 77%
See 3 more Smart Citations
“…Additionally, Castelo et al (2016) demonstrated the interaction between different types of electrical stimuli, as sine or quadratic waves, and electroejaculation using ring or strip electrode apparatus with better results than those reported by Mollineau et al (2008Mollineau et al ( , 2010. The authors obtained 70% of ejaculates, with 57% of ejaculates containing spermatozoa, when using the protocol with the ring electrode associated with sinusoidal stimuli (Castelo et al, 2016). However, Martinez et al (2013) obtained better results using four brown agouti (D. azarae) and obtained 100% success in semen collection.…”
Section: Art For Male Agoutimentioning
confidence: 77%
“…In a subsequent study using the same electroejaculation protocol, but starting at 2 V, an efficiency of 40% of ejaculates containing spermatozoa was obtained (Mollineau et al, 2010a). Additionally, Castelo et al (2016) demonstrated the interaction between different types of electrical stimuli, as sine or quadratic waves, and electroejaculation using ring or strip electrode apparatus with better results than those reported by Mollineau et al (2008Mollineau et al ( , 2010. The authors obtained 70% of ejaculates, with 57% of ejaculates containing spermatozoa, when using the protocol with the ring electrode associated with sinusoidal stimuli (Castelo et al, 2016).…”
Section: Art For Male Agoutimentioning
confidence: 84%
See 2 more Smart Citations
“…Physical restraint was done using hand nets. ey were then anaesthetized using ketamine (dose rate of 35 mg/kg) and xylazine (dose rate of 5 mg/kg) intramuscularly and maintained using quarter dose top-ups when they were coming out of the anaesthesia [24]. Anaesthetic drugs such as ketamine hydrochloride (dose rate of 35 mg/kg) and xylazine hydrochloride (Bomazine 2%, 35 mg/ml) were used at a dose rate of 5 mg/kg to sedate animals [25] ( Table 3).…”
Section: Physical and Chemicalmentioning
confidence: 99%